Scope of Valtellina Cableways in Wood-extraction in the Himalayas - Bhalla, B. K. (Indian Forester, 1968)
Recently, some attempts have been made to extract wood from the outer steep Hill-slopes of the Himalayas, with the help of the sky-line cable-cranes. In the far interior, where further transportation lines do not exist or are not economical of use, cableways may, in many cases, fill the bill and render logging of wood possible. So far, only the so called gravity conveyors or gravity ropeways have, to a very limited extent, been commissioned for the purpose. Performance of these units is generally examined, especially vis-a-vis the efficiency, the Valtellina cableways, under the same circumstance., may be capable of. As the Valtellina system is rather new to the logging practices in the country, it is described in some detail, inserting illustrations, where considered useful in enhancing the clarity of the text.